Examining the Mechanical Influences Upon the Sciatic Nerve at the Sciatic Nerve-Hamstring Muscle Interface During Active and Passive Knee Extension - Ellis, R; Fox, J; Hitt, JR; Langevin, H; Henry, SM (The World Confederation for Physical Therapy (WCPT), 2015)
Background: Ultrasound imaging has been used to examine movement of the peripheral nervous system in response to normal body movements and therapeutic exercises, such as neural mobilisation. Researchers have clearly established that peripheral nerves must be able to move in relation to their surrounding interfacing tissues. However, to date the mechanical influences that these interfacing tissues have upon nerve movement has yet to be determined. Purpose: We sought to examine the different mechanical influences that the surrounding hamstring muscles have upon the sciatic nerve during lower limb movements. A better understanding of the mechanical influences imposed upon the sciatic nerve, from surrounding tissues, would be beneficial to then examine these relationships in clinical populations including lumbar-related leg pain. Methods: A cross-sectional, observational laboratory study was conducted in ten healthy participants (2 males, 8 females; age 24 ± 5 years (mean ± SD); height 169 ± 7 cm; weight, 65 ± 9 kg; body mass index, 23 ± 3 kg/m2) who underwent knee extension movements (active and passive) in upright sitting and side-lying positions. High-resolution ultrasound imaging was used to assess lateral displacement of the sciatic nerve and hamstring muscles (superficial and deep regions). Ultrasound elastography was used to calculate the shear strain between the sciatic nerve-hamstring muscle interface. Electromyography was used to assess the electrical activity of the hamstring muscles during the active and passive limb movements. Range of motion of the pelvis, hip and knee joints was measured with inertial sensors in order to standardize the limb movements among participants. Results: In both the sitting and side-lying positions, passive knee extension resulted in greater differential lateral displacement of the sciatic nerve versus the hamstring muscles along with greater shear strain at the sciatic nerve-hamstring muscle interface when compared to active knee extension. Conclusion: The findings of the study suggest that the greatest amount of differential lateral displacement between the sciatic nerve and the hamstring muscles occurs during passive knee extension compared to active knee extension. Furthermore, this greater differential movement was associated with increased sciatic nerve-hamstring muscle shear strain in the passive compared to the active condition. Implications: Treatment interventions, such as neural mobilisation exercises, employ either active of passive limb movements to induce peripheral nerve movement in disorders where nerve movement is believed to be compromised. Knee extension, whether active or passive, is commonly utilised to induce movement of the sciatic nerve relative to the interfacing hamstring muscles. It would appear from this research that although passive knee extension resulted in greater movement of the sciatic nerve relative to the hamstring muscles, this was accompanied by an increase in nerve-muscle interface shear strain. In many clinical populations where nerve movement is believed to be compromised, it may be clinically prudent to avoid increases in shear strain as this may cause adverse effects from an already mechanosensitised nervous system. Keywords: Sciatic nerve, ultrasound, elastography Funding acknowledgements: Nil.